An integrated strategy for pathogen surveillance unveiled Xylella fastidiosa ST1 outbreak in hidden agricultural compartments in the Apulia region (Southern Italy) - Daniele Cornara; Donato Boscia; Giusy D’Attoma; Michele Digiaro; Angela Maria Ligorio; Giuliana Loconsole; Serena Anna Minutillo; Vito Montilon; Francesco Palmisano; Gianvito Ragone; Maria Rosaria Silletti; Vincenzo Verrastro; et al. (European Journal of Plant Pathology, 2025)
Annual surveillance programs for the plant pathogenic bacterium Xylella fastidiosa are implemented in Europe as part of the preventive phytosanitary strategies enforced to face the emergence of the detrimental infections reported in olives in southern Italy. The programs include inspections and sampling of host plants by prioritizing those showing suspicious symptoms or those known to be highly susceptible to different strains and subspecies of the bacterium. In the framework of these programs numerous outbreaks have been unraveled, with several strains and subspecies found to infect a relatively large host range in France, Spain, Portugal and Italy. Here we report the results of an integrated surveillance approach implemented in the Apulia Region (southern Italy), where a conventional survey program on host plants is complemented by monitoring and testing for X. fastidiosa the insect vectors. In the framework of this program, bacterium-positive spittlebugs were intercepted in the Xylella -free area of the region, close to one of the most relevant Italian table grape production district. Such findings prompted further investigation to identify the bacterial reservoir in the host plants. Almond and grapevine were found to be the most frequently infected hosts, with infections caused by isolates of X. fastidiosa subspecies fastidiosa ST1. Investigations are ongoing to assess the extent and history of the outbreak, to assess and estimate the potential impacts, and define the best options for its containment.